Penanganan Daerah Rawan Longsor Dengan menggunakan Metode Shotcrete - Putra, Aji Permana; Septanto, Djoko; Praja, Sumantri W. (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
Railway travel safety is an important component in rail transportation. The reliability of the railroad infrastructure is one of the points to support the safety of railroad operations. Lintas Bandung - Cikampek is a cross that has varied geographical contours where right-left rail roads have hills and slopes so that the area between Purwakarta Station - Ciganea Station is a landslide-prone area. As happened in the field there was an avalanche at KM 107 + 100 - KM 107 + 300 which caused disruption to train travel. In addition, improper handling of landslides will cause other potential dangers. The handling of the landslide slope in KM 107 + 100 - KM 107 + 300 uses steel tape from the used rails because the landslide is considered to be less than optimal and is looking for other ways to handle landslides. looking for comparisons compared to using the shotcret method. In this study, we tested the landslide handlers that have been carried out by comparing the handling carried out in accordance with the existing provisions between the steel plaster method of the rail used with the shotcrete method. The cause of landslides is due to a steep angle of 65⁰ with a peak height of 15 meters. The impact on crossing is applied to taspat 5 km / hour to anticipate sudden landslides. From the results of the analysis, it was found that the shotcrete method was considered capable of handling landslide-prone areas in KM 107 + 100 - KM 107 + 300. However, for the handling that had been carried out using steel plaster from used rails. However, this handling is considered not optimal because of the limited number of rails around vulnerable areas, resulting in plaster walls that can still make material exit to the railroad tracks.